Inhibitory effect of uranyl nitrate on DNA double-strand break repair by depression of a set of proteins in the homologous recombination pathway. Issue 5 (26th July 2017) - Jin, Feng; Ma, Teng; Guan, Hua; Yang, Zhi-Hua; Liu, Xiao-Dan; Wang, Yu; Jiang, Yi-Guo; Zhou, Ping-Kun
Abstract : Occupational and environmental exposure to uranium has been confirmed to cause tissue injury and carcinogenesis. Abstract : Occupational and environmental exposure to uranium has been confirmed to cause tissue injury and carcinogenesis. As a heavy metal from actinide series, the chemical and radiological toxicities of uranium jointly induce the detrimental effects. However, the mutual action and mechanism of both forms of toxicities still need to be further elucidated. DNA double-strand break (DSB) is a fundamental cause of cell death or genomic instability induced by ionizing radiation. Herein, we investigate the effect of uranyl nitrate on the cellular function of DNA damage response and intrinsic DSB repair on the aspect of chemical toxicity. The results indicated that uranyl ion increased the accumulation of nuclear DNA DSBs in a dose-dependent manner. Both homologous recombination (HR) and non-homologous end joining (NHEJ) pathways of DSB repair were affected by the uranyl ion. The inhibition of DSB repair efficiency is attributed to the depression of a set of critical repair proteins, particularly those for the HR pathway such as ATM, BRCA1, RPA80 and EXO1. The available data enable us to imagine that the chemical toxicity of uranium leads to inhibition of cellular DNA repair capability, which can further aggravate its radiological toxicity.